Awareness of Oral Cancer in a Northwestern Nigerian State: Assessing the Knowledge, Opinion, and Practice of Traditional Healers and Herbalists. (18th December 2013) - Adebola, Rafael A.; Bamgbose, Babatunde O.; Adeoye, Joshua B.; Amole, Taiwo G.
Abstract : Background : Traditional healers/herbalists remain one of the most accessible and popular options of care to people suffering from cancers particularly at the community level in Nigeria. The majority of patients with oral cancer present at the terminal stage after exploring unorthodox care. This study assesses the awareness of oral cancer among traditional caregivers in Kano State, Northwestern (NW) Nigeria. Methods : Self-administered, structured questionnaires were administered to a cross section of 21 traditional caregivers. Results : Of the 21 traditional caregivers studied, the majority (66.7%) had never heard of oral cancer and only 7 (33.3%) were aware. The level of knowledge on oral cancer was assessed using a scoring system classifying respondents as having adequate (>50%) or inadequate (<50%) knowledge. There was a significant educational status gap as respondents with informal education had lesser knowledge than that of their counterparts who had formal education (61.9% versus 19.0%) ( P = 0.012). Conclusions : It is important to have allied healthcare providers informed about oral cancer, as their knowledge and awareness of oral cancer and its risk factors, which were low in our study, are vital in prevention and early detection. Impact : This study provides an insight into oral cancer prevention using traditional herbalists who are popular caregivers for those seeking health-related solutions.